A Viability Quantitative PCR Dilemma: Are Longer Amplicons Better? - Van Holm, Wannes (Appl Environ Microbiol, 2021)
The development of viability quantitative PCR (v-qPCR) has allowed for a more accurate assessment of the viability of a microbial sample by limiting the amplification of DNA from dead cells. Although valuable, v-qPCR is not infallible. One of the most limiting factors for accurate live/dead distinction is the length of the qPCR amplicon used. However, no consensus or guidelines exist for selecting and designing amplicon lengths for optimal results. In this study, a wide range of incrementally increasing amplicon lengths (68 to 906 base pairs [bp]) was used on live and killed cells of nine bacterial species treated with a viability dye (propidium monoazide [PMA]). Increasing amplicon lengths up to approximately 200 bp resulted in increasing quantification cycle (C(q)) differences between live and killed cells while maintaining a good qPCR efficiency. Longer amplicon lengths, up to approximately 400 bp, further increased the C(q) difference but at the cost of qPCR efficiency. Above 400 bp, no valuable increase in C(q) differences was observed. IMPORTANCE Viability quantitative PCR (v-qPCR) has evolved into a valuable, mainstream technique for determining the number of viable microorganisms in samples by qPCR. Amplicon length is known to be positively correlated with the ability to distinguish between live and dead bacteria but is negatively correlated with qPCR efficiency. This trade-off is often not taken into account and might have an impact on the accuracy of v-qPCR data. Currently, there is no consensus on the optimal amplicon length. This paper provides methods to determine the optimal amplicon length and suggests an amplicon length range for optimal v-qPCR, taking into consideration the trade-off between qPCR efficiency and live/dead distinction.